Popularisation of Experimental Archaeology in the Activity of Harjis - Project under the Patronage of the Institute of Archaeology of the University of Lodz (PL) - Katarzyna Badowska; Wojciech Rutkowski (EXARC Journal)
This article outlines our experiences gained during the implementation of activities at the Society of Experimental Archeology Harjis. Our society aims to recreate dress, weaponry and the realities of the Przeworsk culture, that is, people living in the first centuries of Common Era in the territory of present-day Poland. In scientific activity, we are mainly dealing with experimental archaeology by performing experiments in the field of handicrafts such as blacksmithing, carpentry, leathercraft, weaving and pottery. Practical experiments that we carry out are preceded by the interpretation of historical and archaeological sources. We also carried out statistical surveys in the field of ethno-archaeology. We run tests on replicas of various types of weapons that were used in prehistory. The project is complemented by an attempt to reconstruct the nutritional management of Przeworsk culture and, as a result, reproduce the ‘Barbarian’ cuisine. Despite its great potential, experimental archaeology in Poland is still one of the less understood and accepted methods of science. It is struggling with the need to find new ways of popularisation. In this paper we present our methods of disseminating the history and archaeology that we practice.